The prognostic value of CHA2DS2-VASc and GRACE risk scores in patients with ACS - George Trantalis; Konstantina Aggeli; Konstantinos Toutouzas; Andreas Synetos; George Latsios; Maria Drakopoulou; Vasiliki Penesopoulou; Chrysoula Patsa; Dimitrios Tousoulis (Hellenic Journal of Cardiology, 2019)
Objective: Cardiovascular diseases are the first cause of death in western societies. Therapeutic interventions in the individual patient should be guided by the so-called ischemic risk of this patient. Purpose: The aim of the study was to study the ischemic prognostic scores GRACE and CHA2DS2-VASc, in patients underwent angioplasty to highlight which best predicts better the ischemic risk. Methods: Consecutives patients who underwent Percutaneous Coronary Intervention (PCI) due to Acute Coronary Disease, or elective PCI in one centre in Athens, Greece, where included in the study. The GRACE score and the CHA2DS2-VASc score were calculated. Results: 667 patients participated in the study with an average age of 61 ± 11 years and were followed-up for 2 years. The GRACE score and its predicted incidence at 3 years, was compared to the CHA2DS2-VASc score. CHA2DS2-VASc score was able to show a marginally better prognosis of future ischemic events, with an AUC of 0.624 vs 0.608 of the GRACE score. Conclusions: In our study, The CHA2DS2-VASc score managed to predict, marginally better, the appearance of MACCE over GRACE, in patients with angioplasty. Keywords: CHA2DS2-VASc, ACS patients